Isolated growth hormone deficiency in children with vertically transmitted short stature: What do the genes tell us? - Plachy, Lukas; Amaratunga, Shenali Anne; Dusatkova, Petra; Maratova, Klara; Neuman, Vit; Petruzelkova, Lenka; Zemkova, Dana; Obermannova, Barbora; Snajderova, Marta; Kolouskova, Stanislava; Sumnik, Zdenek; Lebl, Jan; et al. (Frontiers in Endocrinology, 2023)
Introduction The growth hormone deficiency (GHD) diagnosis is controversial especially due to low specificity of growth hormone (GH) stimulation tests. It is therefore believed that children diagnosed with GHD form a heterogeneous group with growth disorder frequently independent on GH function. No study evaluating the complex etiology of growth failure in children with diagnosed GHD has been performed thus far. Aims To discover genetic etiology of short stature in children with diagnosed GHD from families with short stature. Methods Fifty-two children diagnosed with primary GHD and vertically transmitted short stature (height SDS in the child and his/her shorter parent <-2 SD) were included to our study. The GHD diagnosis was based on growth data suggestive of GHD, absence of substantial disproportionality (sitting height to total height ratio <-2 SD or >+2 SD), IGF-1 levels <0 for age and sex specific SD and peak GH concentration <10 ug/L in two stimulation tests. All children were examined using next-generation sequencing methods, and the genetic variants were subsequently evaluated by American College of Medical Genetics standards and guidelines. Results The age of children at enrollment into the study was 11 years (median, IQR 9-14 years), their height prior to GH treatment was -3.0 SD (-3.6 to -2.8 SD), IGF-1 concentration -1.4 SD (-2.0 to -1.1 SD), and maximal stimulated GH 6.3 ug/L (4.8-7.6 ug/L). No child had multiple pituitary hormone deficiency or a midbrain region pathology. Causative variant in a gene that affects growth was discovered in 15/52 (29%) children. Of them, only 2 (13%) had a genetic variant affecting GH secretion or function (GHSR and OTX2). Interestingly, in 10 (67%) children we discovered a primary growth plate disorder (ACAN, COL1A2, COL11A1, COL2A1, EXT2, FGFR3, NF1, NPR2, PTPN11 [2x]), in one (7%) a genetic variant impairing IGF-1 action (IGFALS) and in two (12%) a variant in miscellaneous genes (SALL4, MBTPS2). Conclusions In children with vertically transmitted short stature, genetic results frequently did not correspond with the clinical diagnosis of GH deficiency. These results underline the doubtful reliability of methods standardly used to diagnose GH deficiency.